Pengaruh Layanan SAMSAT Keliling dan Penegakan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak di Kantor SAMSAT Tebing Tinggi - Dewi, Kumala Vera; Nainggolan, Putri Insyirah Indriana (Accounting Progress, 2024)
The aim of this research is to determine and analyze the influence of mobile SAMSAT services and enforcement of tax sanctions on taxpayer compliance. The population of this research is the countless number of taxpayers in the city of Tebing Tinggi. By using the Cochran formula, the sample results obtained were 96 respondents. Researchers used a sampling technique using the Accidental Sampling technique. The data collection technique is to use a questionnaire distributed to research respondents. The data analysis used is simple linear regression analysis with the help of SPSS for Windows software. The research results show that partially the mobile SAMSAT service has a positive and significant effect on taxpayer compliance and the enforcement of tax sanctions has a positive and significant effect on taxpayer compliance. Apart from that, simultaneously mobile SAMSAT services and enforcement of tax sanctions have a positive and significant effect on taxpayer compliance.